Matching types of Social Media Sites (SNSs) to motives and profile of youth in Malaysia - Wok, Saodah; Misman, Norealyana (2014)
Social network sites (SNSs) have been used to bring people close to each other across the globe, especially the youth. It is important to find out the matching of types of SNSs to the motives for using them and toward fitting the profile of youth in Malaysia for the SNSs concerned. Specifically, this study tries (1) to find out the types of SNSs subscribed by youth, (2) to gauge the frequency of using the SNSs per week, (3) to rank the motives for using the SNSs, and (4) to compare the differences between youth profile for using the SNSs. A survey was conducted to among youth, aged 17-40 years old, nationwide, using a self-developed questionnaire. A total of 703 respondents were gathered for the study. Data were analyzed using Statistical Package for Social Sciences (SPSS) WIN 20. The respondents of the study were represented by a slightly more male than female, mainly Malays, mostly single, with Islam as their religion, adolescents, doing their first degree, and were students. Based on the youth profile, results revealed that there were differences between various youth demographic characteristics and the types of SNSs that they subscribed to. The top three SNSs that youth subscribed to were Facebook, Yahoo and Skype. Almost one-third of them used them daily. Most of the SNSs were used for social, followed by education, and communication motives. Specifically, Twitter was also used for social, communication and entertainment motives while blog was used for religious, education, business, and politics motives. The study is applying both the social networks theory and information seeking theory so that youth would be motivated to equip themselves with the vast knowledge available and accessible in the SNSs for their own benefits, not merely for social networking.